Transcriptomic Analysis Identifies Differentially Expressed Genes (DEGs) Associated with Bolting and Flowering in Radish (Raphanus sativus L.) - Nie, Shanshan; Li, Chao; Wang, Yan; Xu, Liang; Muleke, Everlyne M.; Tang, Mingjia; Sun, Xiaochuan; Liu, Liwang (Frontiers in Plant Science, 2016)
Abstract The transition of vegetative growth to bolting and flowering is an important process in the life cycle of plants, which is determined by numerous genes forming an intricate network of bolting and flowering. However, no comprehensive identification and profiling of bolting and flowering-related genes have been carried out in radish. In this study, RNA-seq technology was applied to analyze the differential gene expressions during the transition from vegetative stage to reproductive stage in radish. A total of 5,922 differentially expressed genes (DEGs) including 779 up-regulated and 5,143 down-regulated genes were isolated. Functional enrichment analysis suggested that some DEGs were involved in hormone signaling pathways and the transcriptional regulation of bolting and flowering. KEGG-based analysis identified 37 DEGs being involved in phytohormone signaling pathways. Moreover, 95 DEGs related to bolting and flowering were identified and integrated into various flowering pathways. Several critical genes including FT, CO, SOC1, FLC and LFY were characterized and profiled by RT-qPCR analysis. Correlation analysis indicated that 24 miRNA-DEG pairs were involved in radish bolting and flowering. Finally, a miRNA-DEG-based schematic model of bolting and flowering regulatory network was proposed in radish. These outcomes provided significant insights into genetic control of radish bolting and flowering, and would facilitate unraveling molecular regulatory mechanism underlying bolting and flowering in root vegetable crops.